Investigating Tourists’ Perspectives On English Verbal Communication Of Tour Guides At Pulau Banyak, Aceh Singkil - Syafnaliza Liza; Dewi Kesuma Nasution (UMSU, 2021)
The aim of study is to investigate tourists’ perspective on English verbal communication of the tour guides at pulau banyak.. This study used descriptive qualitative method in analyzing the data. Verbal Communication consist can be found and use on tourist guide to tourist foreign. And to reason for the used of communication between researcher and tourists . Tourist Guide are people who provide assistance, information about cultural, historical and contemporary heritage about people organized tours and individual client in educational pleces, Tourist attraction, religious and historical sites, museum, and in places from other significant interests. And Tourist is person travelling in a certain period in place he visits( Yoeti : 1999 ). Therefore, the tourist need someone to help in giving detail information releted to the place, know as tour guide. That have good verbal communication to tourist understand what tour guide talk about it. it was found that the first tour guide produced (Fair ) for Accuracy, (Fair ) for Fluency and (Very Good ) for Comprehensibility . and the second tour guide produced (Fair) for accuracy, (Good ) for Fluency and (Very good ) for Comprehensibility. It means the most dominant types of verbal communication that used on the conversation by both tour guide is Comprehensibility.